EFFICACY OF BIOAGENTS ON THE INCIDENCE OF , SEED GERMINATION AND SEEDLING VIGOUR INDEX OF BLACK GRAM (Journal of Plant Disease Sciences, 2024)
Black gram is one of the important legume crops in India. It is a favorable pulse crop since it thrives better in all the seasons as a sole and intercrops or fallow crop. It is being infected by many phytopathogens. Among the phytopathogens, the leaf spot caused by Alternaria alternata is a major disease, distributed worldwide and considered as the most serious one its management with chemical fungicides exhibit residual toxicity in the soil. It is therefore felt that, it is very essential to develop an effective, cheap and environmentally safe non-chemical method for the management for the pathogen. The biological control using antagonistic microorganisms offer a practical and economical alternative for management of plant pathogens. Hence the present investigation was conducted to test the efficacy of native antagonists of Trichoderma harzianum and Trichoderma asperellum for the management of Alternaria alternata. Among the tested bioagents, Trichoderma harzianum @ 10 gm/kg found most effective having minimum incidence of mycoflora (10.00 %), highest seed germination (89.33 %) and SVI (1786.6) over untreated control by artificially inoculation method. Whereas, by naturally infected seeds with different mycoflora which were tested for efficacy of bioagents, Trichoderma asperellum @ 10 gm/kg found most effective having highest seed germination (88.00 %) and SVI (1990.0) over untreatedcontrol.
Keywords: Black gram; Alternaria alternata; Bioagents; Vigour Index